Role of right ventricular involvement in acute myocarditis, assessed by cardiac magnetic resonance. (15th November 2018) - Aquaro, Giovanni Donato; Negri, Francesco; De Luca, Antonio; Todiere, Giancarlo; Bianco, Francesco; Barison, Andrea; Camastra, Giovanni; Monti, Lorenzo; Dellegrottaglie, Santo; Moro, Claudio; Lanzillo, Chiara; Scatteia, Alessandra; et al.
Abstract: Objectives: Right ventricular (RV) myocarditis (MY) is unrecognized, and its prevalence is unknown. We evaluated the prevalence of RV involvement in acute MY and its association with cardiac events (cardiac death, cardiac arrest, ventricular assist device, transplantation, and appropriate ICD intervention). Methods: We enrolled 151 patients who underwent cardiac magnetic resonance for clinical suspicion of acute MY. The CMR protocol included T2-STIR images for edema detection, post-contrast cine-SSFP for hyperemia detection and late gadolinium enhancement (LGE) images. Results: Signs of RV MY were found in 27 patients (17.8%): RV edema at T2-STIR in all of these 27 patients; RV LGE was detected in 11 patients (7.3%). The median RV myocardial segment involved was 2 (1–3). In 13 patients, RV edema was in direct continuity with LV edema of septum and inferior wall or with anterior septum and anterior wall. In 2 patients RV myocarditis was found without any signs of LV involvement. Patients with RV MY had higher RV end-diastolic volume index ( p  = 0.04) and RV mass index ( p  = 0.03), and lower RV ejection fraction ( p  < 0.001) than others. At Kaplan-Meier survival curve patients with RV MY had more cardiac events than those without RV involvement ( p  = 0.015). RV involvement, anteroseptal LGE and RV LGE were associated with cardiac events. Conclusion: RV involvement in acute MY is more frequent than previously hypothesized. RV MY was associated with cardiac events. Highlights: Right ventricular myocarditis at magnetic resonance was in 17.8% of patients myocarditis Patients with right ventricular myocarditis had worse prognosis than those without. Right ventricular myocarditis was an independent predictor of worse prognosis.